Maritime Museums Online Presence: Actual Value and Challenges - Elena BELLIO; Umberto ROSIN; Francesco CASARIN (Communications of International Proceedings, 2023)
In the macro-area of contemporary tourism, the coastal one can count on a multiplicity of resources, not only natural, human and physical, but also cultural. Maritime museums have recently been recognized as an important lever for the sustainable development of coastal areas. The main objective of this short paper is to map all the Mediterranean Maritime Museums specific features and the challenges that are emerging today. Through an exploratory approach, this research lays the groundwork for identifying the key variables for a long-lasting sustainable development. In a prospective view, the research would like to foreshadows the identification of the most relevant factors related to performance indices. Activating a virtuous cycle between the museum specific features and the territory in which it is located, allows museums to create long-term, multi-dimensional and multi-stakeholder value. This study contributes to the literature on culture and value creation, providing suggestions for managers, scholars, policymakers and practitioners alike. Findings are focusing on a specific category of cultural institution but can easily be extended to any other kind of museum.
Keywords: maritime museums; value; business strategy; sustainable development; tourism